Avaliação da influência da espessura do revestimento argamassado e do carregamento no comportamento da alvenaria frente a altas temperaturas - Souza, Rodrigo Périco de (Universidade do Vale do Rio dos Sinos, 2017)
Masonry is one the most commonly used constructive systems in Brazil, granted the availability of materials, knowledge of the technique and low cost. Due to the growth acceleration programs of the country, several residential buildings were built under this system, with structural function. Concomitant to this movement came into force the housing performance standard, ABNT NBR 15575:2013, which sets requirements and criteria for buildings, among which resides fire safety within buildings. Under this scenario, the following gaps in technical studies are highlighted, the behavior of structural masonry when submitted to high temperatures, the influence of loading on plane deformations found on wall systems, and the influence of mortar coating on the behavior of panels subject to fire. Seeking to contribute to this segment, this study aimed to identify what parameters affect the behavior of masonry concerning high temperatures. For that, masonries constituted of a same ceramic block were evaluated, their internal coating was varied (0, 15 and 25 mm of thickness) and the external was fixed with 25 mm, through tests with and without application of loading of 10 tons force per meter. The standard ABNT NBR 5628:2001 was used for this analysis, with and without loading, using a standardized oven. It should be noted that the tests were performed on real scale structural wall systems, thus allowing for the verification of thermal insulation, leak-tightness, passing of gasses and smoke, as well as structural stability. From the results, it was noticed that there is influence of the thickness of mortar coating and the loading on the behavior of the masonry. The walls with loading presented smaller deformations in comparison with those without loading. Comparing the walls without internal coating, the reduction was of 27.5%. The walls with 15mm of coating on the external wall displayed a reduction of 58.1% and the walls with 25 mm, a reduction of 41.0%. It was observed that, as the coating thickness increased, the plane deformations decreased, passing from 40 mm to 29 mm by the 240 min. Regarding mortar coating, the thermal insulation properties of the walls were improved significantly. The walls without lading and with coating of 25 mm on the internal face presented a reduction of external temperature of 43.3%. The walls with loading and coating of 25 mm indicated a decrease of 23.8%, as well as a modification of their FRS.
Keywords: Alvenaria estrutural; Segurança contra incêndio; Desempenho; Structural masonry; Fire safety; Performance; ACCNPQ::Engenharias::Engenharia Civil